Access Control Mechanisms and Their Role in Preventing Unauthorized Data Access: A Comparative Analysis of RBAC, MFA, and Strong Passwords - Edrian S. Abduhari; Tadzher C. Shaik; Alsimar B. Adidul; Jimrashier H. Ladja; Ersin S. Saliddin; Akshay J. Adin; Fradzkhan A. Rumbahali; Alnadzri B. Sali; Jumadam M. Jemser; Shernahar K. Tahil (HM Publisher, 2025)
In today's digital landscape, the protection of sensitive data from unauthorized access is a critical concern for organizations of all sizes. Robust access control mechanisms are essential for maintaining data security and preventing breaches. This study conducted a comparative analysis of three widely used access control methods: Role-Based Access Control (RBAC), Multi-Factor Authentication (MFA), and Strong Passwords. The research employed a mixed-methods approach, combining a quantitative analysis of simulated data with a qualitative review of recent literature. The Access Control Simulation Environment (ACSE) was developed to generate data on the effectiveness of each access control method in preventing unauthorized access attempts. The qualitative component involved a systematic review of Scopus-indexed publications from 2018 to 2024, focusing on the strengths, weaknesses, and best practices associated with each method. The simulation data revealed that MFA provided the highest level of protection against unauthorized access, followed by RBAC and then Strong Passwords. The qualitative analysis identified key strengths and weaknesses of each method, highlighting the importance of contextual factors in selecting the most appropriate access control mechanism. In conclusion, the findings underscore the need for a layered approach to access control, combining multiple methods to achieve optimal security. While MFA offers the strongest protection, RBAC and Strong Passwords remain crucial components of a comprehensive security strategy. The study provides practical recommendations for organizations seeking to implement and optimize access control mechanisms to mitigate the risk of unauthorized data access.